Implementasi Model Incremental Pada Pengembangan Aplikasi Pengenalan Rempah-Rempah Berbasis Game - Rachman, Andy; Efendi, Yanuar; Nugroho, Hendro; Sulistyowati, Sulistyowati; Alala, Pratama Sandi; Rozi, Nanang Fakhrur (INTEGER: Journal of Information Technology, 2023)
Currently, technology is the most important part of human life, especially for the people of Indonesia. Its existence is very helpful in resolving any existing shortcomings. The fields of energy that utilize Information and Communication Technology include business and services, government, tourism, and education. The use of technology in education can be seen in the current state of education in Indonesia, starting from the use of the internet, the development of online learning applications, the availability of digital books, and the development of game-based educational media. Researchers develop game-based learning applications in introducing spices in Indonesia. The focus of the users in this study were elementary school students in Grade 6. The researcher applied an incremental model in developing an educational game application for the introduction of spices. The Students at Gempolkerep State Elementary School, Ngudikidul Village, Gedek District, Mojokerto, East Java, have implemented an Educational game application. The application has also been assessed by 44 respondents consisting of 34 elementary school students and ten application development expert teams. Respondents must answer twelve questions to evaluate the usefulness of educational game applications. Assessment of application usability uses a Likert Scale based on the Usability Factor of ISO 9126-3. The effectiveness of the application developed by the researcher for Gempolkerep State Elementary School students is 83% and gets an assessment from the expert team of 77%.